Konvergensi IFRS di Indonesia: Apakah Relevansi Nilai Relatif dan Inkremental Informasi Akuntansi Terdampak? - Dewi, Anisah Kusuma; Kristanto, Ari Budi (Jurnal Dinamika Akuntansi dan Bisnis, 2018)
This paper investigates whether the value relevance of earnings information and equity information have changed as the IFRS (International Financial Reporting Standard) convergence taken place in Indonesia. The qualitative characteristic is viewed in the perspective of relative value and incremental value relevance. Theoretically, the earnings value relevance should increase, and equity lost its value relevance pursuant the IFRS convergence. The financial data of manufacturing companies in Indonesian Stock Exchange during 2008-2016 were sorted purposively based on companies with complete financial statement and stock price data during 8 consecutive years. This study uses regression analysis to test the hypotheses. It was found that earning and equity information contain value relevance. Moreover, there is no evidence to support the hypotheses that IFRS convergence decrease earnings value relevance and decrease equitys value relevance.